Agricultural policy reforms and trade liberalisation in the Mediterranean Basin : A partial equilibrium analysis of regional effects on the EU-27 and on the Mediterranean Partner Countries - Kavallari, Aikaterini; Justus Liebig University Giessen (My University, 2008)
This study examines agricultural trade flows around the Mediterranean basin and gives insights on the likely impacts of agricultural policy reforms on the Mediterranean agriculture. Currently trade relationships are characterised by complexity due to the numerous bilateral regional trade agreements between the Mediterranean countries. The most important of them are the Euro-Med Agreements - also known also as Barcelona Agreement - an initiative of the EU which started in 1995 and aims to establish a free trade area after 2010 with all non-EU Mediterranean countries. The analysis showed that the interests of the involved countries to intensify their trade relationships are diverging and the expected changes of the agricultural policy create uncertainty for the future of agriculture around the Mediterranean. Based on the theory of applied welfare economics, this study analyses empirically the impacts of different policy scenarios on Mediterranean countries by using an extended and modified version of the trade policy model, AGRISIM. The simulation results indicated that the CAP reform of Mediterranean commodities affects only very slightly the markets for cotton, olive oil and tobacco and then only within the EU Mediterranean member states. The enlargement of the EU to include Bulgaria and Romania only affects these two countries. Trade liberalisation, either within the framework of the WTO or within the Barcelona Agreement leads to overall welfare gains, with the effects being of a small magnitude. Differences are observed between the net trade performance of the countries across the north and the south coast of the Mediterranean with the former being more favoured than the later. The Mediterranean EU Member States show a positive evolution of their net trade performance but an overall deterioration of the net trade of the EU s Mediterranean Partner Countries is observed, particularly evident for commodities such as olive oil and oranges. The WTO liberalisation has more marked effects only on EU markets leading to a reduction in the internal supply of highly protected commodities, such as beef, while the demand for these commodities increases. This point, that liberalisation would not be harmful, but on the contrary it would be beneficial for the Mediterranean agricultural markets due to the positive welfare effects should be taken into consideration by policy makers.

Diese Studie analysiert den Agrarhandel im Mittelmeerraum und versucht die Auswirkungen geänderter agrarpolitischer Rahmenbedingungen auf den mediterranen Agrarsektor herauszuarbeiten. Zurzeit sind die Handelsbeziehungen komplex wegen der zahlreichen Präferenzabkommen auf bilateraler Ebene zwischen den mediterranen Ländern. Einer der wichtigsten regionalen Handelsabkommen ist die Euro-Mediterrane Partnerschaft, bekannt auch als Barcelona Abkommen: eine Initiative der EU aus 1995 mit dem Ziel eine Freihandelszone zwischen der EU und alle Nicht-EU Mittelmeerländer ab 2010 zu gründen. Auf der Basis der angewandten Wohlfahrtsökonomie untersucht diese Arbeit die Auswirkungen geänderter agrarpolitische Rahmenbedingungen auf den Agrarsektor der Mittelmeerländer. Die empirische Analyse wird mit einer erweiterten und angepassten Version des partiellen Multi-Markt-Multi-Regionen Gleichgewichtmodells AGRISIM durchgeführt. Die Simulationen zeigen, dass die Reform der Gemeinsamen Agrarpolitik der EU für Baumwolle, Olivenöl und Tabak nur sehr geringe Auswirkungen auf die entsprechenden Märkte der EU-Mittelmeerländer hat. Die EU-Erweiterung mit Bulgarien und Rumänien wirkt ebenso nur auf diese zwei Länder. Handelsliberalisierung, sowohl im Rahmen der WTO (World Trade Organisation) als auch im Rahmen des Barcelona-Abkommens führt zu Wohlfahrtsgewinnen, aber die Effekte auf die Märkte sind sehr klein. Unterschiede gibt es zwischen den nord- und den südmediterranen Staaten, wenn es um den Nettohandel geht. Die mediterranen EU Mitgliedsländer zeigen eine positive Handelsbilanz, während die Partnerländer der EU eine negative Handelsbilanz, vor allem für Hauptexportprodukte wie Orangen und Olivenöl ausweisen. Die Effekte der WTO Liberalisierung sind nur auf den EU Märkten höher. Hier sind ein Rückgang des Angebots und eine Steigerung der Nachfrage für hochprotektionierte Produkte wie Rindfleisch zu erwarten. Dieser Aspekt, dass Liberalisierung nicht den Agrarmärkten schadet, sondern positiv auf den Mediterranen Agrarsektor wirkt, sollte bei den Entscheidungsträgern besonders beachtet werden.
Agrarpolitikreformen und Handelsliberalisierung im Mittelmeer : Ein Partiellgleichgewichtsanalyse der regional Effekte auf die EU-27 und der Mediterrane Partner Länder
Keywords: Agrarpolitik; Handelsliberalisierung; partielles Gleichgewichtsanalyse; Mittelmeerraum; Barcelona Abkommen; agricultural policy; trade liberalisation; partial equilibrium analysis; Mediterranean basin; Barcelona Agreement; ddc:320